Identifying and predicting food parenting practice profiles among Canadian parents - Claire N. Tugault-Lafleur; Olivia De-Jongh González; Teresia M. O'Connor; Sheryl O. Hughes; Louise C. Mâsse (BMC, 2021)
Abstract Background Food parenting practices (FPP) can affect children's eating behaviours, yet little is known about how various FPP co-occur. The primary aim was to identify profiles of FPPs use among Canadian parents. Secondary aims included examining sociodemographic correlates of FPP profiles and evaluating whether children's eating behaviours differed across FPP profiles. Methods Parents (n = 799) of 5-12-year-old children completed a validated FPP Item Bank and the Children's Eating Behaviour Questionnaire. Latent Class Analysis (LCA) was used to identify distinct FPP profiles. Regression analyses were used to explore associations between FPP profiles, sociodemographic variables (race, sex and education) and children's eating behaviours (emotional overeating, food responsiveness, food fussiness and satiety responsiveness). Results LCA revealed 6 FPP profiles: healthy eating environment, high engagement, reactive, high structure, controlling and low engagement. Relative to their non-White counterparts, White parents were more likely to belong in the healthy eating environment, high structure and low engagement profiles. Relative to fathers, mothers were more likely to fall in the healthy eating environment compared to low engagement profile. Parents with some post-secondary education were more likely to belong in the healthy eating environment, high structure and reactive profiles compared to the controlling profile. Emotional overeating and food responsiveness scores were lowest for healthy eating environment, high structure, low engagement profiles. Parents in the healthy eating environment profile also reported lower food fussiness scores compared to parents in the high engagement, high structure, reactive and controlling profiles. Conclusions Findings suggest that a continuum of 6 FPP profiles may be present among Canadian parents, representing parents who use either all (high engagement), some (healthy eating environment, reactive, high structure, controlling) or little (low engagement) of the FPP examined. Future longitudinal research should evaluate how various FPP profiles influence the development of children's eating behaviors, dietary intakes and weight status.